Disciplines are not the Enemy: Three Insights from an Interdisciplinary Project on Everyday Security - Benenson, Zinaida; Eckhardt, Dennis; Freiling, Felix; Pöhls, Heinrich C. (2026)
We observe that the computer security community seems to regard interdisciplinarity as a non-problem. Indeed, by now this disci pline possesses many links to other disciplines, such as economics, law or sociology. Angela Sasse pioneered the interdisciplinarity in computer se curity by creating connections to psychology and ergonomics more than 25 years ago. Here, we focus on reflexivity of interdisciplinary research in computer security, as it has not received much attention so far. We do this by contributing three experiences with interdisciplinarity from a large funded research project on everyday digital security in Germany. Our three experiences cover (a) different levels of interdisciplinary in teraction (termed small and big), (b) the ambivalent role of a jointly developed (standardized) terminology, and (c) the need to localize in terdisciplinary interaction not only in time but also in space. Together, these experiences bring new insights into the interdisciplinary work on people and security initiated by Angela Sass